Genomic analysis for managing small and endangered populations: a case study in Tyrol Grey cattle - Mészáros, Gábor; Boison, Solomon A.; Pérez O'Brien, Ana M.; Ferenčaković, Maja; Curik, Ino; Da Silva, Marcos V. Barbosa; Utsunomiya, Yuri T.; Garcia, Jose F.; Sölkner, Johann (Frontiers in Genetics, 2015)
Analysis of genomic data is increasingly becoming part of the livestock industry. Therefore the routine collection of genomic information would be an invaluable resource for management of breeding programs in small, endangered populations. The objectives of this project were to analyse 1. linkage disequlibrium decay and the effective population size; 2. Inbreeding level and effective population size (NeROH) based on runs of homozygosity (ROH); 3. Prediction of genomic breeding values (GEBV) within and across breeds. In addition, the use of genomic information for breed management is discussed. The study was based on all available genotypes of Tyrol Grey AI bulls. ROHs were derived based on regions covering at least 4 Mb, 8 Mb and 16 Mb regions, with the corresponding mean inbreeding coefficients 4.0%, 2.9% and 1.6%, respectively. The NeROH was 125 (NeROH>16Mb), 186 (NeROH>8Mb) and 370 (NeROH>4Mb), indicating strict avoidance of close inbreeding in the population. The genomic selection was developed for and is working well in large breeds. Contrary to the expectations, the accuracy of GEBVs with very small within breed reference populations were very high, between 0.13-0.91 and 0.12-0.63, when EBVs and dEBVs were used as pseudo-phenotypes, respectively. Subsequent analyses confirmed the high accuracies being heavily influenced by parent averages. Multi-breed and across breed reference sets gave inconsistent and lower accuracies. Genomic information may have a crucial role in management of small breeds. It allows to assess relatedness between individuals, trends in inbreeding and to take decisions accordingly. These decisions would be based on the real genome architecture, rather than conventional pedigree information, which can be missing or incomplete. We strongly suggest the routine genotyping of all individuals that belong to a small breed in order to facilitate the effective management of endangered livestock populations.